2014
DOI: 10.1111/jre.12225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dynamic three‐dimensional culture on osteogenic potential of human periodontal ligament‐derived mesenchymal stem cells entrapped in alginate microbeads

Abstract: For the first time human mesenchymal stem cells obtained from periodontal ligaments encapsulated in alginate microbeads were cultured in a bioreactor system. This combination could represent a promising strategy to create a cell-based smart system with enhanced osteogenic potential useful for many different dental applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Finally, immobilizing cells within polymeric matrices represents an advantageous 3D culture system for mass production in bioreactors [87,88] by maintaining the pluripotency of ESCs and induced pluripotent stem cells [89,90]. 3D spherical culture systems allow enrichment of cancer stem-like cells for cancer research and therapy development [91], and allow the production of a readily scalable liver cell biomass for the development of a bioartificial livers [92].…”
Section: Reviewmentioning
confidence: 99%
“…Finally, immobilizing cells within polymeric matrices represents an advantageous 3D culture system for mass production in bioreactors [87,88] by maintaining the pluripotency of ESCs and induced pluripotent stem cells [89,90]. 3D spherical culture systems allow enrichment of cancer stem-like cells for cancer research and therapy development [91], and allow the production of a readily scalable liver cell biomass for the development of a bioartificial livers [92].…”
Section: Reviewmentioning
confidence: 99%
“…For example, dental‐derived stem cells PDLSCs and HGMSCs encapsulated in RGD‐ (arginine–glycine–aspartic acid tripeptide) coupled alginate microsystems greatly enhanced the proliferation up to 4 weeks of the culture period with a subsequent increase in the expression of osteogenic markers, like runt‐related transcription factor 2 (RUNX‐2), alkaline phosphatase (ALP), and osteocalcin. The ability to form mineral deposits were comparable with HBMSCs in these cells . In another study, human adipose stem cells embedded in collagen‐alginate microcarriers injected subcutaneously formed functional adipose tissue .…”
Section: Alginate Microcarriers In Tissue Engineering Applicationsmentioning
confidence: 81%
“…Most importantly, the spherical structure allows a larger surface area with high diffusibility and mobility of cells or drugs that need to be delivered. It has been shown that there was 50% enhancement in ectopic bone formation when cells delivered in microcarriers than those cultured in monolayers or 2‐D cultures …”
Section: Microcarriers As a Mode Of Cell Delivery Vehiclesmentioning
confidence: 99%
“…With respect to the concentrations of biomaterial used for the preparation of microfibers (sodium alginate, gelatin, and UBM), the selected amounts were chosen on the basis of a large number of previously published observations (Penolazzi et al, 2010, 2012; Mazzitelli et al, 2013; Angelozzi et al, 2015; Vecchiatini et al, 2015). For instance, alginate is typically used in the concentration range comprised between 0.5 and 2.5% (w/v) depending on the stiffness required by the specific application of the gel.…”
Section: Resultsmentioning
confidence: 99%